FISTULA IN ANO-A REVIEW - Kumar Uttam; B.B.Khuntia (International Journal of Applied Ayurved Research, 2017)
Fistula in ano is one of the common and notorious disease among all anorectal disorder.It is recurrent nature of the disease which makes it more and more difficult for treatment.It produces inconveniences in routine life.It causes discomfort and pain that creates problem in day to day activities.Bhagandar resembles with the description of fistula in ano as described in modern medical science.Bhagandar is described in all major classical text books of Ayurveda.Acharya sushruta ,the father of surgery has included Bhagandar as one among Ashtamahagada.In this present review article article describes pathophysiology,investigate modalities and treatment option for fistula in ano in Ayurveda and modern medical science.